Analisis Kinerja Keuangan PT. MNC Sky Vision Tbk pada Periode 2019-2023 - Karissa Meina Maulida; Chris Petra Agung; Vera Intanie Dewi (Movere Journal, 2025)
Indonesia's media and entertainment industry has experienced significant growth; however, PT. MNC Sky Vision Tbk faced challenges due to declining subscribers from 2019 to 2023. This led to a decrease in revenue and an increase in net losses. This study evaluates the company's financial performance using financial ratio analysis, horizontal and vertical analysis, and cash flow analysis based on financial statements and annual reports. The findings indicate a downward trend in financial performance, driven by declining sales without a proportional reduction in the cost of revenue, with fixed asset depreciation being the largest expense. Most financial ratios show deterioration and reduced cash inflows from operating activities have heightened the company’s liquidity risk. To address these issues, the company should focus on increasing sales, improving accounts receivable collection, and optimizing fixed asset management to enhance financial stability and ensure long-term business sustainability.